Perfectionism, over commitment to work and burnout in employees seeking workplace counselling - Philp, Michael; Egan, Sarah; Kane, Robert (John Wiley & Sons Ltd., 2012)
Perfectionism is linked to a range of psychological disorders. Burnout is an important construct in the working population and has been found to overlap with related constructs such as depression. There has been limited research conducted between perfectionism and burnout. This study aimed to examine the link between perfectionism and burnout and if procrastination and over commitment to work were mediators of the relationship. There were 69 participants recruited who were seeking counselling from a counselling firm, providing employee assistance services. The results indicated that procrastination was not a significant mediator of the relationship between concern over mistakes (CM) perfectionism and burnout. There was a significant mediating relationship found, where overcommitment to work mediated the relationship between CM perfectionism leading to burnout. The implications of the study in terms of interventions for employees suffering burnout, and directions for future research in regards to the relationship between perfectionism and burnout are considered.